The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016 22nd IEEE International Symposium on Asynchronous Circuits and Systems (ASYNC) 2016
DOI: 10.1109/async.2016.19
|View full text |Cite
|
Sign up to set email alerts
|

The Metastable Behavior of a Schmitt-Trigger

Abstract: Schmitt-Trigger circuits are the method of choice for converting general signal shapes into clean, well-behaved digital ones. In this context these circuits are often used for metastability handling, as well. However, like any other positive feedback circuit, a Schmitt-Trigger can become metastable itself. Therefore, its own metastable behavior must be well understood; in particular the conditions that may cause its metastability.In this paper we will build on existing results from Marino to show that (a) a mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 13 publications
(41 reference statements)
1
22
0
Order By: Relevance
“…As a consequence, the S/T must be susceptible to metastability. This intuitive argument has been more formally supported by Marino [1] already, and more recently Steininger et al [2] have detailed several practically relevant scenarios where metastability may occur and where it may not. While there exist analytic solutions to calculate certain properties such as the threshold voltages [3], none have been presented so far regarding metastability.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…As a consequence, the S/T must be susceptible to metastability. This intuitive argument has been more formally supported by Marino [1] already, and more recently Steininger et al [2] have detailed several practically relevant scenarios where metastability may occur and where it may not. While there exist analytic solutions to calculate certain properties such as the threshold voltages [3], none have been presented so far regarding metastability.…”
Section: Introductionmentioning
confidence: 81%
“…For this purpose we replace the load capacitance by a voltage source and actually measure the current through the latter (visible in the second code line). In comparison to the approach from [2], where the authors performed transient analysis and picked V out , this is considerably faster but serves the same purpose, albeit we get I out as a result instead. To compare the results of static and transient simulation (see Section III-B) in Fig.…”
Section: A Static Analysis Of Grid Points (Map)mentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid oscillating behavior for inputs close to the reference, Schmitt-Trigger (S/T) stages [4] are employed instead whose hysteresis behavior makes them ignore irrelevant voltage fluctuations. However, it has been shown that for certain input traces a S/T can become metastable as well [5], [6]. Following the lessons learned from synchronizers, one may ask whether the cascading of S/Ts is again effective in reducing the risk of metastable upsets.…”
Section: Fig 1 S/t Hysteresismentioning
confidence: 99%
“…4) until V m reaches V L,2 (V in = V 1 ) the second S/T will start to switch and can be driven into metastability in the same way as the first one. While keeping both S/Ts in metastability, which is either possible with very precise or very fast control of V in (for a more detailed explanation see [6]), the output values between LO and HI shown in Fig. 7 are reachable.…”
Section: Moving Into Metastabilitymentioning
confidence: 99%